2017
DOI: 10.5489/cuaj.4408
|View full text |Cite
|
Sign up to set email alerts
|

Intraureteral lidocaine for ureteral stent symptoms post-ureteroscopy: A randomized, phase 2, placebo-controlled trial

Abstract: Introduction: Ureteral stent and ureteral manipulation-related pain is a significant complication for patients undergoing ureteroscopy. Herein, we report a phase 2, randomized trial to assess efficacy of direct instillation of intraureteral lidocaine in reducing postoperative pain and ureteral stent symptoms. Methods: We performed a randomized, double-blinded trial of patients undergoing elective ureteroscopy for ureteral calculi. Patients were randomized to direct instillation of 2% lidocaine plus bicarbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although ureteroscopy has been conventionally performed under GA or spinal or under conscious sedation, the procedure, for lower ureteral calculi, has also been described using only 2% lignocaine jelly topically in the urethra 14 and bladder. Conceptually, the benefit of extrapolating this topical anaesthesia, from the bladder into the ureter including the PCS, has been studied by Roberts et al 3 for relief of post-Ureterorenoscopy (URS) stent-related pain. The same has not been studied with respect to performing ureteroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ureteroscopy has been conventionally performed under GA or spinal or under conscious sedation, the procedure, for lower ureteral calculi, has also been described using only 2% lignocaine jelly topically in the urethra 14 and bladder. Conceptually, the benefit of extrapolating this topical anaesthesia, from the bladder into the ureter including the PCS, has been studied by Roberts et al 3 for relief of post-Ureterorenoscopy (URS) stent-related pain. The same has not been studied with respect to performing ureteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects such as postdural puncture headaches occur in 0.1%e17.3% of patients, delaying convalescence. 2 The present study was aimed at finding the safety and efficacy of performing ureteroscopy and laser lithotripsy, using alkalinised local anaesthetic solution 3,4 topically, in the entire accessible urinary tract. The perioperative analgesia was provided by a single intramuscular Non Steroidal Anti Inflammatory Drug (NSAID).…”
Section: Introductionmentioning
confidence: 99%
“…Topical anesthetics have also been shown to potentially reduce pain. In a 2017 randomized study of intra-ureteral lidocaine, Roberts et al found that the direct instillation of lidocaine into the ureter did not significantly improve pain symptoms after URS ( 11 ). Overall, studies evaluating interventions to impact intra-operative analgesic requirements are limited and the impact on post-operative pain remains unclear.…”
mentioning
confidence: 99%